2016
DOI: 10.4103/0974-8490.182912
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and antioxidant activities of stem bark extract and fractions of Petersianthus macrocarpus

Abstract: Background:Petersianthus macrocarpus (Lecythidaceae) is widely used in the folk medicine in Nigeria to relieve pain and fever associated with malaria. This study evaluated the analgesic and antioxidant activities of the methanol extract and fractions of the stem bark of the plant.Materials and Methods:The analgesic activity was determined in mice using hotplate and acetic acid-induced writhing models. Morphine sulphate (5 mg/kg, i.p.) and aspirin (100 mg/ml, p.o.) were used as reference analgesic agents. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
4
2
0
2
Order By: Relevance
“…The extracts could be assumed as practically safe and non-toxic. This result is in agreement with Olorunnisola et al (2012), Parasuraman et al (2014), Ugbogu et al (2016) and Adesegun et al (2016) that reported that the acute toxicity of plants could be considered practically non-toxic and safe above the oral administration of 5000 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The extracts could be assumed as practically safe and non-toxic. This result is in agreement with Olorunnisola et al (2012), Parasuraman et al (2014), Ugbogu et al (2016) and Adesegun et al (2016) that reported that the acute toxicity of plants could be considered practically non-toxic and safe above the oral administration of 5000 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
“…All the rats were allowed free access to food and water throughout the duration of the study. Thirty per cent of the highest dose of LD 50 was based on the selection of the graded doses for the sub-acute toxicity study, as also reported by Adesegun, Celestina and Coker (2016).…”
Section: Sub-acute Toxicity Studiesmentioning
confidence: 95%
“…This may be attributed to the incomplete absorption brought about by inherent factors limiting absorption in the gastro intestinal tract (Dennis, 1984). The present study agrees with the work done by Prasanth et al, (2015); Ugbogu et al, (2016); Kofi et al, (2014) and Adesegun et al, (2016);. Bruce, (2006) reported that any substance with LD 50 estimated to be greater than 2000-5000 mg/kg body weight given orally could be considered to be of low toxicity and safe.…”
Section: Resultssupporting
confidence: 93%
“…[ 2 4 5 ] Polyphenols are mainly responsible for the astringency of many beverages and fruits (especially unripe), such as tea,[ 6 ] coffee,[ 6 ] wine,[ 7 ] aronia berry juice,[ 8 ] and persimmon. [ 9 ] Meanwhile, they also exist in many herbs. [ 10 11 ] Astringency is not only a tactile sensation but also a special flavor.…”
Section: Introductionmentioning
confidence: 99%